2007
DOI: 10.1111/j.1468-036x.2007.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Overconfidence and Investor Size

Abstract: "Recent research documents that institutional or large investors act as antagonists to other investors by showing opposite trading behaviour following the disclosure of new information. Using an extremely comprehensive official transactions data set from Finland, we set out to explore the interrelation between investor size and behaviour. More specifically, we test whether investor size is positively (negatively) correlated with investor reaction following positive (negative) news. We document robust evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 28 publications
(33 reference statements)
1
19
0
Order By: Relevance
“…Only a few studies examine overconfidence among professional investors. 8 Ekholm and Pasternack (2008) find that overconfidence decreases with investor size. O'Connell and Teo (2009) use data on the trading behavior of institutional currency traders and find that they increase risk-taking following gains.…”
Section: Introductionmentioning
confidence: 90%
“…Only a few studies examine overconfidence among professional investors. 8 Ekholm and Pasternack (2008) find that overconfidence decreases with investor size. O'Connell and Teo (2009) use data on the trading behavior of institutional currency traders and find that they increase risk-taking following gains.…”
Section: Introductionmentioning
confidence: 90%
“…Chen et al (2007) show that Chinese individual investors appear to make worse trading decisions and have more trading mistakes than institution investors. Odean (1998), Ekholm and Pasternack (2008) also confirm that institutional investors' trading decisions are less biased than the individuals in the behavioral aspects.…”
Section: Introductionmentioning
confidence: 58%
“…More specifically, high income and high educational level have a statistically significant association with the level of overconfidence (Table 6). In spite of the fact that some studies have supported a negative relationship between experience and overconfidence (Ekholm and Pasternack, 2008;Gervais and Odean, 2001;Locke and Mann, 2001;Menkhoff et al, 2006, Christoffersen andSarkissian, 2002), analysis has shown that investment experience is positively correlated with overconfidence). In the same line, the majority of the studies have found similar findings (Frascara, 1999;Kirchler and Maciejovsky, 2002;Glaser et al, 2003;Griffin and Tversky, 1992;Obernarcher and Osler, 2008;Chen et al, 2004).…”
Section: Overall Sample Analysismentioning
confidence: 99%
“…De Long et al (1990) and Wang (2001) 4 Investment experience positively affects overconfidence Gervais and Odean (2001), Locke and Mann (2001), Menkhoff et al (2006), Philip (2007), Ekholm and Pasternack (2008), Frascara (1999), Maciejovsky and Kirchler (2003), Glaser et al (2003), Griffin and Tversky (1992) and Obernarcher and Osler (2008) 5…”
Section: Associations Developmentmentioning
confidence: 99%